Joint custody or alternating custody - Giorge Andre Lando; Bruno Leonardo Pereira Lima Silva (Revista de Direito, 2023)
This article discusses about joint custody or alternating custody and the doubt about the doctrine that became mandatory. This research aims to answer the following problem: Does Law No. 13,058/2014 regulate the Mandatory Joint Custody or the Mandatory Alternating Custody? In order to introduce the problem, we aim to compare the features of joint custody and alternating custody, with the enactment of Brazilian Law No. 13,058/2014. We also aim to present the importance of the principle of the best interests of the child, to study the dimension of the family power, andto highlight the concepts and features of joint custody compared to the alternating custody in order to, finally, analyze the kind of guard that was regulated by Brazilian Law No. 13,058/2014. This is a theoretical research, based on the legal work of relevant authors in this field. Moreover, in this paper, we also address topics such as the parents' relationship with their children, family power, and custody and its types.